THE ROLE OF N. I. VAVILOV AND VIR’S SCIENTISTS IN DESERT RECLAMATION - N. I. Dzyubenko; A. A. Kochegina (Труды по прикладной ботанике, генетике и селекции)
The article is devoted to the origins of the fight against desert expansion in Russia and former Soviet Republics of Central Asia and Kazakhstan, and N. I. Vavilov’s plans to solve the complex problems of desert and semi-desert reclamation in the areas of the USSR; afforestation, melioration and climatic studies; problems of southern industrial crops; formation of sustainable forage crop cultivation for livestock, and establishment of oases. The research on this topic was conducted by the Repetek Sand Desert Station (run by VIR from 1925 to 1941) with a supporting site in the Kara-Bogaz-Gol, the Aral Experimental Station (organized in 1933), the Turkmen Research Station of VIR in Kara-Kala (established in 1927), the Azerbaij ani branch VIR on the Apsheron Peninsula (organized in 1926). Investigations of the desert were started by the Repetek Sand Desert Station, the only one in the world involved in the stationary study of sands. Its staff examined the typology of sands in the southeastern Karakum, the nature of their movement, conducted edaphic, botanical and hydrological studies in the area of construction of the Karakum Channel. They were the first in the world to suggest using phytomelioration by psammophytes of moving sands, conducted successful experiments in the introduction of black saxaul, calligonum and sandy acacia into cultivation and discovered the wet condensation subsurface horizon creating reserves of moisture in the sand dunes. In 1932, when the Bureau of Deserts was founded, its coordination plan served as the foundation for the deployment of investigations throughout sands of Russia and Central Asian Republics. Huge work was carried out on integrated geobotanical, geological, hydrological studies of soil and vegetation of deserts and semi-deserts (Astrakhan, Pridon, Terek-Kuma, Uilskie, Naryn sands, the Karakum, Kyzylkum, Betpakdala, Mangyshlak, Aral Sea region, Muyunkum, etc.), as well as evaluation of their suitability for rainfed and irrigated agriculture, productivity of natural pastures, hayfields, saxaul forests. Valuable food, fodder and technical plants were studied. Scientists of the Aral Experimental Station received the State Prize for the development of rainfed, irrigated and trench cultivation of cereals, forages, vegetables, fruits and ornamental crops and for making oases in a desert environment. They selected, bred, propagated and introduced into the agriculture of Kazakhstan more than 40 varieties of different agricultural crops. Development and implementation of the technology for consolidation and afforestation of sands in the southeast and east of the European part of the country and development of the first cultivar of saxaul Priaralskiy 1 also won the State Prize. After the transfer of the Aral Experimental Station under the jurisdiction of the Republic of Kazakhstan, expeditions collecting desert plant genetic resources, their study and building up a collection of worldwide genetic resources of desert crops were continued. At the present level, to assess salt tolerance of alfalfa transcriptome analysis was applied. Employees of the Department of Perennial Forage Crop Genetic Resources of VIR took part in the mapping of arid areas and sustainable fodder plant distribution for the Internet publication “Interactive Agricultural Ecological Atlas of Russia and Neighboring Countries Economic Plants and their Diseases, Pests and Weeds.” On the basis of the world collection of desert agricultural cultivars breeders of the Aral Experimental Station, as well as the institutions of the country and some foreign countries developed numerous varieties.